2014
DOI: 10.1080/15226514.2014.922925
|View full text |Cite
|
Sign up to set email alerts
|

The Tolerance and Accumulation ofMiscanthus Sacchariflorus(maxim.) Benth., an Energy Plant Species, to Cadmium

Abstract: Miscanthus sacchariflorus (Maxim.) Benth. is a metallophyte suitable for the phytoremediation of mine wastes. The tolerance and accumulation of M. sacchariflorus to cadmium was studied by pot experiments. The results showed that O2·- generation rate, plasma membrane permeability and MDA content of M. sacchariflorus leaves increased with increasing Cd concentrations in soil, but significant effect was only observed when Cd concentrations were ≥50 mg·kg(-1). SOD and POD activities increased initially but decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
1
16
1
Order By: Relevance
“…In the present study, shoot concentration, root concentration, and TF of Cd in the eight Miscanthus species/cultivars varied in the ranges 11.8-29.3 mg/kg, 64.9-361.3 mg/kg, and 0.06-0.28, respectively, at a soil total Cd 48.1 mg/kg. In another study investigating MS, its shoot concentration, root concentration and TF of Cd varied in the ranges 0.92-18.36 mg/kg, 2.34-64.77 mg/kg, and 0.50-0.29, respectively, at soil total Cd concentrations from 1 to 100 mg/kg (Zhang et al 2015), consistent with results reported here. In addition, reported tolerance of Miscanthus spp.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, shoot concentration, root concentration, and TF of Cd in the eight Miscanthus species/cultivars varied in the ranges 11.8-29.3 mg/kg, 64.9-361.3 mg/kg, and 0.06-0.28, respectively, at a soil total Cd 48.1 mg/kg. In another study investigating MS, its shoot concentration, root concentration and TF of Cd varied in the ranges 0.92-18.36 mg/kg, 2.34-64.77 mg/kg, and 0.50-0.29, respectively, at soil total Cd concentrations from 1 to 100 mg/kg (Zhang et al 2015), consistent with results reported here. In addition, reported tolerance of Miscanthus spp.…”
Section: Discussionsupporting
confidence: 88%
“…The MS tolerance to and low accumulation of Cd may in part be due to Cd induced malate secretion (Guo et al 2016. Results by Zhang et al (2015) also suggested that MS had a strong ability to tolerate Cd but a poor ability to translocate Cd from root to shoot (Pidlisnyuk et al 2014). Regarding Zn, it was reported that the aerial biomass and Zn accumulation of MG was much higher than M. sinensis, consistent with results herein, although the reported higher shoot Zn concentration and TF for M. sinensis than for MG differ from the present results (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To cope with heavy metal stress, M. floridulus and M. sacchariflorus reconcile their photosynthetic efficiency and antioxidant capability to varying degrees. For example, the chlorophyll content and activities of superoxide dismutase and POD are significantly increased under the stress from low concentrations of Pb, Zn, or Cd (Zhang et al., 2015). A variety of beneficial microorganisms are available in the rhizosphere of Miscanthus.…”
Section: Environmental Impactmentioning
confidence: 99%
“…), M. sinensis Andersson, and M. floridulus (Lab.) had the potential to remediate metal(loid)s contamination in soils, and the remediation efficiency was related to plants’ genotype and metal(loid)s type [ 23 , 24 , 25 , 26 , 27 ]. The ability of M. floridulus to accumulate Cd was significantly higher than that of M. sacchariflorus (Maxim.…”
Section: Introductionmentioning
confidence: 99%